Analysis of Non-Formal Education Tutor Capabilities in Exploring Assessment for Science Learning - Darmawan, D.; Yatimah, D.; Sasmita, K.; Syah, R. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2020)
This study aims to explore cognitive assessment techniques based on teaching experience. The method in this study uses a descriptive survey with data collection techniques using purposive sampling of tutors who have taught at PKBM for 5 years. The population in this study were PKBM (Pusat Kegiatan Masyarakat or Community Learning Center) tutors in Jakarta at Package A, Package B, and Package C, namely 158 tutors with details as follows; Package A 45 tutors, Package B 53 Tutors, and Package C 60 tutors. Data collection was done by using question forms and data analysis used descriptive translation to obtain an average frequency of learning assessment techniques. The statistical analysis used Confirmatory Factor Analysis, so that it can be seen directly and indirectly. The results showed that the dominant assessment technique used in non-formal science tutors was a written test that averaged 32 times in one semester. A group of tutors with 5 to 10 years of teaching experience using a variety of assessment techniques. Descriptively, it can be said that the use of the frequency spectrum of cognitive assessment techniques is coupled with experienced tutors with a tendency in written tests. In this study, the results show that the preparation of assessment in non-formal education there is an influence between the preparation of the assessment of the implementation of the assessment. So it is necessary to improve tutor assessment preparation.